A Case Study: Same Day Spontaneous Reduction of a Traumatic Infantile Depressed Skull Fracture. Issue 1 (9th February 2022) - Tang, Kinglam; Chow, Kwan Ho; Po, Yin‐Chung
Abstract: A depressed skull fracture refers to a focal caving of the calvaria. Conservative management in the paediatric population is advised in the absence of brain injury as the deformity will often correct itself as the skull grows over the following months. Herein, we present a rare case of an infantile traumatic depressed skull fracture that spontaneously resolved within 4 hours of the injury. A 9‐month‐old male presented with a 6 mm deep traumatic depressed skull fracture after falling from sofa height. The fracture spontaneously reduced during a crying episode whilst waiting for the CT scan and the subsequent brain CT confirmed complete resolution of the fracture with no brain injury. The child was monitored in the outpatient setting and remained well with no neurological or cosmetic sequalae. It is postulated that the infant's skull plasticity and the increased intracranial pressure (ICP) from his crying allowed for the spontaneous resolution of the skull deformity. This case thus beautifully illustrates the efficacy of watchful waiting in traumatic paediatric depressed skull fractures without underlying neurological injury.